Wine and economics transacting the elixir of life - Marks, Denton; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2015)
Wine and the wine trade are steeped in culture and history; few products have consistently enjoyed both cultural importance and such wide distribution over time--even seen by some as "an elixir of life". While wine has been produced and consumed for centuries, what is distinctive about the economics of wine? Professor Marks's book is an accessible exploration of the economics of wine, using both basic principles and specialized topics and emphasizing microeconomics and related research. Drawing upon economic themes such as International Trade and Public Choice, Wine and Economics also relates economic reasoning to management issues in wine markets. The discussion ranges from economic fundamentals and wine and government, to the challenge of knowing what is in the bottle and the importance of wine as a cultural good. This novel and comprehensive introduction to the subject is an invaluable resource for students, scholars and anyone interested in wine and the wine industry.
1. Introduction -- 2. The relevance of economics -- 3. Comparative advantage and why we transact -- 4. Some basic tools of economics : consumer behavior and demand -- 5. Some basic tools of economics : firm behavior, supply, and equilibrium in a market -- 6. Wine and government -- 7. A closer look at the transaction : how do we know what is in the bottle? -- 8. Wine as a cultural good -- 9. Conclusion.
Includes bibliographical references and index.
Description based on online resource; title from title screen (viewed February 13, 2015).
Keywords: Wine industry; Wine industry -- Economic aspects; Electronic books